Benefits of tropical crops for food security - Vermeulen, Sonja J.; Wollenberg, Eva Karoline (National Academy of Sciences, 2011)
West et al. s recent paper (1) compared tradeoffs of carbon and crop production in temperate and tropical zones. We welcome the empirical evidence in support of agricultural intensification rather than extensification.